Feasibility of progressive strength training implemented in the acute ward after hip fracture surgery. - Lise Kronborg; Thomas Bandholm; Henrik Palm; Henrik Kehlet; Morten Tange Kristensen (PLoS ONE)
Importance Patients with a hip fracture lose more than 50% knee-extension strength in the fractured limb within one week of surgery. Hence, immediate progressive strength training following hip fracture surgery may be rational, but the feasibility unknown. Objective To examine the feasibility of in-hospital progressive strength training implemented in the acute ward following hip fracture surgery, based on pre-specified criteria for feasibility. Design, setting and patients A prospective cohort study conducted in an acute orthopedic hip fracture unit at a university hospital. A consecutive sample of 36 patients, 18 with a cervical and 18 with a trochanteric hip fracture (27 women and 9 men, mean (SD) age of 79.4 (8.3) years) were included between June and December 2012. Intervention A daily (on weekdays) program of progressive knee-extension strength training for the fractured limb, using ankle weight cuffs in 3 sets of 10 repetition maximum loadings. Main outcomes and measures The primary outcome was the change in training load (kg) during the knee-extension strength training. The secondary outcomes were changes in hip fracture-related pain and maximal isometric knee-extension strength. Results The strength training was commenced at a mean of 2.4 (0.7) days after surgery. The training loads (kilograms lifted) increased from 1.6 (0.8) to 4.3 (1.7) kg over 4.3 (2.2) training sessions (P<.001). The maximal isometric knee-extension strength of the fractured limb increased from 0.37 (0.2) to 0.61 (0.3) Nm/kg (P<.001), while the average strength deficit in the fractured limb decreased from 50% to 32% (% non-fractured, P<.001). Only 3 of 212 sessions were not performed because of severe hip fracture-related pain. Conclusion and relevance Progressive knee-extension strength training of the fractured limb commenced in the acute ward seems feasible, and may reduce strength asymmetry between limbs without hip pain interfering. The clinical efficacy needs confirmation in a randomized controlled design. Trial registration ClinicalTrials.gov ID: NCT01616030.